Uso de ferramentas de Mobile Learning nas práticas de aprendizagem: uma revisão narrativa - Oliveira, Elisa Bomfim Rosario de (2025)
The objective is to analyze scientific production on the use of Mobile Learning interfaces in multimodal learning practices through a narrative review of the literature. With an essentially qualitative approach, the research is characterized as exploratory. The analysis was carried out in the Education Resources Information Center (ERIC) database, using peer-reviewed and complete texts published in the last 10 years (2015 to February 2025) as a filter. The searches included the keywords: “Mobile Learning,” “Multimodal Reading,” “E-Readers,” “Educational Technology,” “Educational Innovations,” “Mobile Learning,” and Virtual Learning Environment (VLE), covering research in Portuguese and English from scientific articles, books, book chapters, and experience reports. It contextualizes the concept of the “mobile subject,” the development of Mobile Learning practices, the impacts of digital ecosystems on education, and the benefits and challenges of using mobile interfaces in learning. As a result, trends, gaps, and paths for the development of new methodologies, pedagogical practices, and research on the topic are identified. It concludes that Mobile Learning is a powerful tool that can transform educational practices, promoting the ubiquity and flexibility of learning. It highlights the importance of careful Instructional Design and consideration of multimodality to optimize engagement and teaching effectiveness. The resolutions point to the need for more empirical research on the application of Mobile Learning in different contexts, as well as for the development of educational policies that encourage its conscious and effective use.